If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 = 9x + -21 Reorder the terms: 15 + 3x = 9x + -21 Reorder the terms: 15 + 3x = -21 + 9x Solving 15 + 3x = -21 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 15 + 3x + -9x = -21 + 9x + -9x Combine like terms: 3x + -9x = -6x 15 + -6x = -21 + 9x + -9x Combine like terms: 9x + -9x = 0 15 + -6x = -21 + 0 15 + -6x = -21 Add '-15' to each side of the equation. 15 + -15 + -6x = -21 + -15 Combine like terms: 15 + -15 = 0 0 + -6x = -21 + -15 -6x = -21 + -15 Combine like terms: -21 + -15 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| 1.666+x=-20 | | y=9x+14y+6x+25 | | 22-r=74 | | y=9x+14andy+6x+25 | | z-5z=72-9-z | | rv3/s2 | | 33+1/3c=66 | | 2x^2+4x-49=0 | | -65(z-61)=z-61 | | 1.5x=.833+2 | | 77+75+76= | | 2x+4y-2y+x= | | (w+6)(w-2)= | | 2/9=x/36 | | 8-(x+3)=-2x+9 | | 0=-9k | | -x+32=54 | | 4/7=x/35 | | 4/7=?/35 | | 56=2(10+a) | | -5b-4b=1-5b | | ax-a^2-bx+b^2= | | xaoverc=-1 | | 10.08*62/5 | | 3n+3=4 | | 5y+3x-13+5x= | | 2.5*3+2.5= | | 10.08*32/5 | | 10y+10=0 | | -6x+6x^2= | | 2n+n-19=21 | | ax-a^2=bx-b^2 |